The role of SUMOylation in Liver X Receptor (LXR) transrepression of inflammatory responses - Al-Momani, Razan (2019)
Liver X Receptors (LXRs) are ligand-activated transcription factors that regulate genes involved in lipid metabolism, as well as those concerned with immune and inflammatory responses. SUMOylation of LXRs has been proposed to be central to the anti-inflammatory activity of LXRs in terms of transrepression of inflammatory gene promoters. However, recent work has suggested that SUMOylation-independent transcriptional activation of the lipid transporter ABCA1 can lead to inhibition of inflammatory signalling pathways, thus the mechanism/s by which LXRs inhibit inflammatory responses remains to be fully understood.